Manajemen Beban Kerja, Konflik Kerja Dan Stres Kerja: Pengaruhnya Terhadap Kinerja Karyawan Melalui Kepuasan Kerja Sebagai Intervening Di PT Harapan Teknik Shipyard - Irfad, Andri; Sanusi, Fauji; Mukhsin, Moh. (Faculty of Economics and Business - Universitas Sultan Ageng Tirtaysa, 2021)
This research is motivated by the need for good management of employees in managing workloads, work conflicts and work stress to be able to improve the resulting performance and be strengthened by a better level of job satisfaction. The purpose of the study was to examine the effect of workload management, work conflict and work stress on employee performance through job satisfaction as an intervening. The research was conducted at PT Harapan Teknik Shipyard with a total sample of 58 people. The data was collected using a questionnaire which was then analyzed using the SEM-PLS model which was processed with the SmartPLS application. Based on the results of statistical tests, it is known that there is an influence of work conflict management on employee job satisfaction, there is an effect of job stress management on employee job satisfaction, there is an influence of job satisfaction on employee performance and there is a mediating effect of job satisfaction on the relationship of work conflict management on employee performance. There is a mediating effect of job satisfaction on the relationship between work stress management and employee performance.